2012
DOI: 10.1371/journal.pone.0029693
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Terlipressin on Regional Hemodynamics and Kidney Function in Experimental Hyperdynamic Sepsis

Abstract: Background and AimsAlthough terlipressin (TP) may improve renal function in cirrhotic patients, its use in sepsis remains controversial due to concerns about regional ischemia. We investigated the effects of TP on regional hemodynamics and kidney function in experimental hyperdynamic sepsis.MethodsWe studied thirteen merino ewes in a university physiology laboratory using a randomized controlled cross over design. We implanted flow probes around the pulmonary, circumflex coronary, superior mesenteric, renal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…19 Finally, infusion of efferent arteriolar vasoconstrictors, such as angiotensin II and vasopressin, during experimental hyperdynamic sepsis improve MAP, GFR, and urine output despite reduced global RBF. 20,21 This observation further supports the role of prevailing efferent arteriolar relaxation in septic AKI.…”
Section: Glomerular Hemodynamics In Septic Acute Kidney Injurysupporting
confidence: 69%
“…19 Finally, infusion of efferent arteriolar vasoconstrictors, such as angiotensin II and vasopressin, during experimental hyperdynamic sepsis improve MAP, GFR, and urine output despite reduced global RBF. 20,21 This observation further supports the role of prevailing efferent arteriolar relaxation in septic AKI.…”
Section: Glomerular Hemodynamics In Septic Acute Kidney Injurysupporting
confidence: 69%
“…Renal function was better preserved by selepressin, particularly when administered early. In experimental and clinical studies of septic shock, AVP, terlipressin, or [Phe 2 ,Orn 8 ]vasotocin was shown to increase urine output and creatinine clearance ( 14 , 41 , 42 ). Because selepressin cannot induce V 2 receptor-mediated antidiuresis, due to its very high selectivity for the V 1A receptor ( 8 , 10 ), restoration of arterial pressure may have contributed to the preserved renal perfusion and the increased urine output.…”
Section: Discussionmentioning
confidence: 99%
“…77 These findings from the Vasopressin and Septic Shock Trial are largely consistent with large mammal preclinical studies of SA-AKI. 75,78 CONCLUSIONS In adult human beings, early septic shock is associated more commonly with hyperdynamic circulation and is likely to be associated with high-flow-low-pressure renal circulation. Timely reversal of these circulatory abnormalities with vasoconstrictors may reverse early hemodynamically mediated renal dysfunction, and higher blood pressure targets may be justified in patients with pre-existing hypertension.…”
Section: Vasopressorsmentioning
confidence: 99%